PELATIHAN METODOLOGI PENELITIAN PENDIDIKAN: ETNOGRAFI, EVALUASI, PENELITIAN DAN PENGEMBANGAN (R & D) BAGI DOSEN UNIVERSITAS TIMOR LOROSA`E: - - Waruwu, Marinu; Tri Satyawati, Sophia; Dwikurnaningsih, Yari; Ismanto, Bambang; Wasitohadi; Ezverenzha Lelatobur, Lovely; Saputri Lamba, Septhy; Falerery Pesulima, Flawelna; De Araujo Tilman, Alexandra (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2025)
Community service activities were carried out for lecturers at the Education, Arts and Humanities Faculty, Universitas Nasional Timor Lorosa’ e. This activity aimed to improve lecturers' skills in understanding the concepts and practices of educational research methodologies (research and development, evaluation, and ethnography). The training was carried out online using the Zoom meeting application and WhatsApp. The results of community services show that the level of participant satisfaction with the training quantitatively is 86%, with a very good category. This result is supported by a qualitative evaluation that shows that training runs effectively and efficiently, adds knowledge and skills, is flexible, and encourages independence. This shows that community service activities through online-based training have an impact on increasing lecturers' knowledge to practically apply the concept of research methodology in higher education.